Cyber Warfare And Protection Of Civilian Under International Humanitarian Law - Mian Muhammad Sheraz; Fazli Dayan (Elementary Education Online, 2023)
Cyberspace is shared by the people and military both, and cyber warfare is developing a fifth domain of warfare. The intricate cosmos of cyber warfare nurtures several queries regarding the meanings, variances with other warfare and compatibility with jus ad bellum and jus in bello. The solution of some queries lies in construal of existing law armed conflict and others remain open and without an obvious solution. In this paper we will shed some light on those queries whether current international legal regime can cope with the new form of warfare which has already developed as a fifth domain of warfare.